Los límites de Babel Ensayos sobre la comunicación entre lenguas y culturas - Grupo Alfaqueque (Iberoamericana Vervuert, 2010)
The result of reflection on communication, this book highlights the role of people who facilitate understanding between cultures and languages, setting limits to the unintelligible cacophony that is identified with Babel. Depending on the places and the historical moment, these intermediaries have carried out different tasks, but their figure has always been present in intercultural encounters born of wars, migrations or colonizing ambitions. This study goes from the present, to the near past (the Spanish emigration of 1960-1970) and to a more distant one, the Middle Ages and the Modern Age of discoveries and colonization. It covers diverse scenarios, from Mexico to Araucanía, the Germany that receives emigrants and the medieval kingdoms of Castilla y León. Such examples allow us to understand the hybrid companies that are being set up today in Spain and in many other countries.